Atama – sırtqı kоmpоziciyanıń bir bólegi sıpatında (qaraqalpaq pоvestleri mısalında) - Bekbergenоva, Z.U (ILIM hám JÁMIYET, 2025)
Chapters, parts, titles, epigraphs, prologues, epilogues, etc. occupy an important place in the external composition of prose works. The article examines the role of the title as one of these external compositional tools in shap- ing the architectonics of a literary work and draws relevant conclusions using the example of contemporary Karakalpak short stories.